2016
DOI: 10.3892/mmr.2016.5463
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin and irradiation modifies the activity of ADAM10 and neprilysin in breast cancer cells

Abstract: Angiogenesis, the formation of new blood vessels, is regarded as a key cancer cell property. Endostatin (ES) is a potential antiangiogenic agent and it may be useful when implemented in combination with other cancer therapeutic strategies. The present study investigated the in vitro effects of ES, radiotherapy (RT) or combination therapy (ES + RT) on two important proteases, a disintegrin and metalloproteinase domain‑containing protein 10 (ADAM10) and neprilysin (NEP) in 4T1 mouse breast cancer cells and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For instance, ionizing radiations induced upregulation of ADAM10 and MMP2 proteases, as well as the amount of soluble MICA secreted by lung cancer cells; notably, the combined treatment of ionizing radiation and MMP inhibitors dramatically increased the surface expression levels of MICA, promoting the recognition and killing of cancer cells by NK cells (68). The effects of ionizing radiations on upregulation of ADAM10 expression levels was also shown in a mouse model of breast cancer (69). In line with these studies, etoposide (a topoisomerase II inhibitor able to activate the DDR), enhanced ADAM10 expression (70).…”
Section: Modulation Of Nkg2d Ligand Shedding In Response To Stressmentioning
confidence: 88%
“…For instance, ionizing radiations induced upregulation of ADAM10 and MMP2 proteases, as well as the amount of soluble MICA secreted by lung cancer cells; notably, the combined treatment of ionizing radiation and MMP inhibitors dramatically increased the surface expression levels of MICA, promoting the recognition and killing of cancer cells by NK cells (68). The effects of ionizing radiations on upregulation of ADAM10 expression levels was also shown in a mouse model of breast cancer (69). In line with these studies, etoposide (a topoisomerase II inhibitor able to activate the DDR), enhanced ADAM10 expression (70).…”
Section: Modulation Of Nkg2d Ligand Shedding In Response To Stressmentioning
confidence: 88%
“…In this line, Aydemir et al indicated that endostatin, an angiogenesis inhibitor derived from type XVIII collagen, enhances the anticancer effects of radiotherapy in BC cells through alteration of SP levels 55 . In a further study, they found that endostatin exerts cytotoxic effects in BC cells by increasing the activity of SP‐degrading enzymes including ADAM10 and NEP 56 . Similarly, it has been suggested that thalidomide, an antiangiogenic agent, through altering the activities of ADAM10 and NEP enzymes induces antiangiogenic effects in 4T1 and 4THMpc mouse BC cell line 57 .…”
Section: Sp‐degrading Enzymes and Bc Tumorigenesismentioning
confidence: 97%
“…As illustrated in Table 1 and Table 2 , RE in combination with RT has also be evaluated in preclinical settings for several non-pulmonary cancer types, such as breast, oesophageal, hepatocellular, colorectal and nasopharyngeal carcinoma [ 127 , 131 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ]. The two in vitro studies on breast cancer cell lines of Aydemir and co-workers confirmed that RE potentiated the anti-tumour effect of RT [ 138 , 139 ]. In their first study, RT alone inhibited the growth of 4T1 (30.81%) and 4THMpc (39.64%) cells, while the addition of RE enhanced the growth inhibition to 83% in 4T1 and 80% in 4THMpc cells [ 138 ].…”
Section: Radiotherapy and Anti-angiogenic Therapy: A Dilemmamentioning
confidence: 99%
“…The latter showed that the combination of RE with RT has the potential to significantly change the microenvironment of oesophageal carcinoma. In parallel, two in vivo studies illustrated that RE improved the radioresponse in oesophageal xenograft mouse model [ 139 , 144 ]. Both studies showed a reduction in MVD on histological tumour sections and a delay in tumour growth in the treatment groups with RE and RT, compared to RT alone.…”
Section: Radiotherapy and Anti-angiogenic Therapy: A Dilemmamentioning
confidence: 99%